Facile transformation of imine covalent organic frameworks into ultrastable crystalline porous aromatic frameworks - Xinle Li (Nature Portfolio, 2018)
Despite recent success in developing new covalent organic frameworks (COFs) materials, synthesis of chemically stable COFs still remains challenging. Here the authors demonstrate a facile strategy that transforms imine-linked COFs into robust porous aromatic frameworks by kinetically fixing the reversible imine linkage via an aza-Diels-Alder cycloaddition reaction.